2015
DOI: 10.1007/s00059-014-4191-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of adiponectin and lipoprotein(a) levels in cardiac syndrome X

Abstract: We detected low adiponectin and high Lp(a) levels in patients with CSX and these findings may be related to the microvascular injury in CSX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Adiponectin levels were measured in 2 studies and were significantly lower in subjects with CMD compared with those without CMD. 68 , 69 Lipoprotein(a) levels were significantly higher is subjects with CMD compared with controls, and lipoprotein(a) was an independent predictor of CMD. 68 Last, in one small study, investigators found that circulating levels of adrenomedullin, a vasodilatory peptide that reduces oxidative stress, correlated with CFR and coronary flow–mediated dilation.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Adiponectin levels were measured in 2 studies and were significantly lower in subjects with CMD compared with those without CMD. 68 , 69 Lipoprotein(a) levels were significantly higher is subjects with CMD compared with controls, and lipoprotein(a) was an independent predictor of CMD. 68 Last, in one small study, investigators found that circulating levels of adrenomedullin, a vasodilatory peptide that reduces oxidative stress, correlated with CFR and coronary flow–mediated dilation.…”
Section: Resultsmentioning
confidence: 92%
“… 68 , 69 Lipoprotein(a) levels were significantly higher is subjects with CMD compared with controls, and lipoprotein(a) was an independent predictor of CMD. 68 Last, in one small study, investigators found that circulating levels of adrenomedullin, a vasodilatory peptide that reduces oxidative stress, correlated with CFR and coronary flow–mediated dilation. 61 Among the biomarkers of endothelial function, data supporting endothelin‐1 appear the most convincing.…”
Section: Resultsmentioning
confidence: 92%
“…With the development of endothelial dysfunction, decrease in microvascular vasodilatation, increase in intracoronary pressure, and decrease in subendocardial perfusion occur, and the patient experiences angina pectoris ( 23 ). Moreover, decreased endogenous nitric oxide and adiponectin, increased plasma endothelin-1, and lipoprotein (a) were observed in CSX patients, and these are all thought to be indicators of endothelial dysfunction and premature atherosclerosis ( 24 , 25 ). We believe that the relationship between vitamin D deficiency and endothelial dysfunction is an explanation to our finding that vitamin D is associated with CSX and the abnormal response to exercise in patients with CSX.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the content of lipoprotein an in patients with microvascular angina is significantly higher than that in normal people, while apolipoprotein a is significantly lower. Apolipoprotein a may be a protective factor [13][14][15][16] . Some studies have also confirmed that lipoprotein associated Phospholipase A2 (Lp PLA 2) can promote the release of inflammatory factors, reduce the production of nitric oxide, and lead to dysfunction of coronary microvascular endothelial cells.…”
Section: Risk Factorsmentioning
confidence: 99%